British scholars of comparative education examining the work and influence of notable 19th and 20th century comparativists - Phillips, David 1944 December 15- (Oxford studies in comparative education, 2020)
This book brings together studies of significant British scholars of comparative education from the 19th and 20th centuries. Providing a unique and detailed examination of the work of the founding British scholars of research in comparative education, British Scholars of Comparative Education considers the legacy of these key figures and emphasises the importance of understanding their achievements. The advancement of research in comparative education has long been driven by the work of key scholars, ensuring it remains a lively area of educational research. This book highlights the pivotal role played by each scholar in driving a progression through humanistic and scientific approaches to new epistemological traditions within the field of comparative education. This in turn reveals critical historical-epistemological transitions that have had lasting impacts on the field. With contributions from leading scholars in the field, this volume will be of great interest to researchers, academics, and scholars in comparative and international education